RF front-end for GNSS software receiver - Teo, Zhi Kun. (2013)
This report will covers the concept and development of a RF Front-End designed for a software receiver and notably in the new civil signal, Global Positioning System (GPS) L5, under the EE4079 Final Year Project. The RF Front End is designed with a filter module and an I/Q demodulator to convert the received signal to a baseband signal.